(untitled) (Global Journal of Medical Research, 2020)
Bevacizumab, a humanized antibody against VEGF, is effective within the treatment of patients with several cancers. However, like several therapeutic agents, important side effects such as arterial thromboembolism, venous thromboembolism, hypertension, neutropenia, proteinuria, and hemorrhage are related to bevacizumab. Thromboembolism is one of the leading causes of morbidity and mortality in patients with cancer. Considerations have arisen relating to the chance of venous and arterial thromboembolism with the novel antiangiogenic agent bevacizumab: a recombinant humanized monoclonal antibody to a vascular endothelial growth factor which is wide employed in cancer treatment.